Menejemen Resiko Bencana Alam Berdasarkan Islam: Satu Kajian Pendahuluan - Muhammad Hilmi Bin Mat Johar; Abd Rahman Bin Hamzah; Badlihisham Mohd Nasir (Fakultas Dakwah dan Komunikasi, Universitas Islam Negeri, Raden Fatah Palembang, 2019)
Abstract: Natural disasters are hot issuesbeing discussed either through print media or electronic media. The natural disasters took place in recent years have created anxieties to the world's population so that many agencies are involved in the search for a wide range of latest and upcoming alternatives to tackle the problems. This catastrophic problem is often associated with the law of the rule of nature but there are some obvious causes by human activity for local development. The concept of destiny is one of the important aspects in the discipline of history, philosophy and religion. There are debates involves the physical and metaphysical nature of the unseen nature and its relation to the existence of God, the relationship of God andhuman, the relationship of God with nature and human relationships with nature. Natural disasters such as landslides, earthquakes, flash floods and so forth are likely the result from greedy human acts in the pursuit of modernization through extreme development. While the disasters had affected our mother nature, it is important for us to implement the precautionary measures to minimize the effects of natural disasters and thus prevent and minimize the impact of losses. Continuing from this analogy, this paper will analyze and provide a framework for disaster risk management proposals in the Islamic perspective. Keyword: Natural disaster, development, flash flood, landslides, prevention